2012
DOI: 10.1073/pnas.1211149109
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular13C pattern in hexoses from autotrophic and heterotrophic C3plant tissues

Abstract: The stable carbon isotope 13 C is used as a universal tracer in plant eco-physiology and studies of carbon exchange between vegetation and atmosphere. Photosynthesis fractionates against 13 CO 2 so that source sugars (photosynthates) are on average 13 C depleted by 20‰ compared with atmospheric CO 2 . The carbon isotope distribution within sugars has been shown to be heterogeneous, with relatively C abundance in their specific precursor C-atom positions. However, the intramolecular isotope pattern in source le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 41 publications
3
69
0
Order By: Relevance
“…Of these three pathways, only the EMP has been closely examined for position-specific 13 C fractionation in ethanol biosynthesis (13,14,18), whereas some data from the RPP are also available (12). These studies clearly demonstrated that fermentation by the EMP route leads to 13 C/ 12 C isotopic ratios for the methyl (CH 3 ) and methylene (CH 2 ) carbon positions that differ depending on the source glucose.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these three pathways, only the EMP has been closely examined for position-specific 13 C fractionation in ethanol biosynthesis (13,14,18), whereas some data from the RPP are also available (12). These studies clearly demonstrated that fermentation by the EMP route leads to 13 C/ 12 C isotopic ratios for the methyl (CH 3 ) and methylene (CH 2 ) carbon positions that differ depending on the source glucose.…”
mentioning
confidence: 99%
“…However, at that time (1961) isotope measurement by mass spectrometry gave only a value for ␦ 13 C g (‰), the global or mean isotope content, and the technique is poorly adapted to the determination of the intramolecular distribution of isotopes. Subsequently, measurement of ␦ 13 C i (‰), the position specific isotope distribution, has proved the first part of the above conclusion to be incorrect (12,18): as yet, evidence is still to be presented that glycolysis proceeds without position-specific isotopic discrimination. To probe this, we have carried out an analysis of ␦ 13 C i (‰) in ethanol from the EMP pathway.…”
mentioning
confidence: 99%
“…In addition, the oxidative deamination of cadaverine should imply an intramolecular kinetic carbon isotope effect (40). As a result, competition between equivalent positions of the symmetrical precursors should select in favor of isotopomers containing 12 C at this position, leading to a 13 C depletion of the C atom bearing the oxygen function (C5 T ) relative to that bound to N (C1″ T ). Both these predictions are not met: on the contrary, C1″ T is depleted relative to C5 T (ΔC5 T − C1″ T = 10.2‰).…”
Section: Resultsmentioning
confidence: 99%
“…The information that can be obtained from examining the global isotope deviations (δ 13 C g ) in whole molecules (14,15) by isotope ratio monitoring by mass spectrometry (irm-MS) is inadequate because this technique, in which the target is combusted to CO 2 in an O 2 -rich atmosphere, has the disadvantage of only determining the average distribution of 13 C among the isotopomers (δ 13 C g ‰). This leads to considerable loss of information about isotope fractionation, because not only are heavy isotopes unevenly distributed within a compound, but position-specific isotopic fractionation at natural abundance is defined by the specific reactions taking place during biosynthesis (12,16,17).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation